Strategies to Obtain Encapsulation and Controlled Release of Small Hydrophilic Molecules - Li, Qi; Li, Xiaosi; Zhao, Chao (Frontiers in Bioengineering and Biotechnology, 2020)
The therapeutic effect of small hydrophilic molecules is limited by the rapid clearance from the systemic circulation or a local site of administration. The unsuitable pharmacokinetics and biodistribution can be improved by encapsulating them in drug delivery systems. However, the high water solubility, very hydrophilic nature, and low molecular weight make it difficult to encapsulate small hydrophilic molecules in many drug delivery systems. In this mini-review, we highlight three strategies to efficiently encapsulate small hydrophilic molecules and achieve controlled release: physical encapsulation in micro/nanocapsules, physical adsorption via electronic interactions, and covalent conjugation. The principles, advantages, and disadvantages of each strategy are discussed. This review paper could be a guide for scientists, engineers, and medical doctors who want to improve the therapeutic efficacy of small hydrophilic drugs.